2021
DOI: 10.1016/j.jbc.2021.100355
|View full text |Cite
|
Sign up to set email alerts
|

Motifs of the C-terminal domain of MCM9 direct localization to sites of mitomycin-C damage for RAD51 recruitment

Abstract: The MCM8/9 complex is implicated in aiding fork progression and facilitating homologous recombination (HR) in response to several DNA damage agents. MCM9 itself is an outlier within the MCM family containing a long C-terminal extension (CTE) comprising 42% of the total length, but with no known functional components and high predicted disorder. In this report, we identify and characterize two unique motifs within the primarily unstructured CTE that are required for localization of MCM8/9 to sites of mitomycin … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 81 publications
(125 reference statements)
0
31
0
Order By: Relevance
“…Previously, several laboratories including ours have shown that MCM8/9 form nuclear foci, upon damage, primarily from DNA crosslinking agents or after direct DSBs induced from ionizing radiation. 24,30,31 This implicates MCM8/9 in HR, but there is limited information investigating a possible role during fork progression/stalling. To directly examine whether MCM8/9 are involved in maintaining genomic instability during replication stress, a C-terminal GFP-tagged MCM9 fusion construct was transfected into WT 293T cells, after which cells were treated with 2 mM hydroxyurea (HU) for 4 hours, and MCM9 foci formation was monitored ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, several laboratories including ours have shown that MCM8/9 form nuclear foci, upon damage, primarily from DNA crosslinking agents or after direct DSBs induced from ionizing radiation. 24,30,31 This implicates MCM8/9 in HR, but there is limited information investigating a possible role during fork progression/stalling. To directly examine whether MCM8/9 are involved in maintaining genomic instability during replication stress, a C-terminal GFP-tagged MCM9 fusion construct was transfected into WT 293T cells, after which cells were treated with 2 mM hydroxyurea (HU) for 4 hours, and MCM9 foci formation was monitored ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7a ) that interacted with and recruited RAD51 to sites of MMC induced DNA damage. 30 Therefore, we sought to investigate the role of this MCM9-BRCv motif in maintaining fork stability after HU treatment using DNA fiber analysis. Interestingly, in the absence of HU, fork stability is restored in 9 KO cells when MCM9(BRCv - ) is transfected, implying that the MCM8/9 complex on its own provides some stabilizing context to active replisomes, possibly through its helicase activity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations